A new way of synthesis of V0.13Mo0.87O2.935 and an investigation on its structural, thermal, and anodic properties - Beyribey, Berceste (SPRINGER, 2013)
V0.13Mo0.87O2.935 powder was obtained by reducing acidified vanadate and molybdate solution at 60 A degrees C by passing hydrogen sulfide gas through the solution. The obtained multicomponent mixed oxide was used as an anode material for the first time in the literature and tested in the solid oxide fuel cell for the temperatures of 700, 750, and 800 A degrees C and the values of 0.38 +/- A 0.06 A/cm(2) and 0.18 +/- A 0.03 W were respectively obtained as current density and power at 800 A degrees C in the cell.
Keywords: V-Mo-O catalyst; Multicomponent mixed oxide; Anodic activity; OXIDE CATALYSTS; MIXED OXIDES; MOO3; OXIDATION; PROPANE; Chemistry